Synthesis and Evaluation of Restricted Access Material-Molecularly Imprinted Polymer Based on Self-Assembly and Sol-Gel Technique - Lv, Yun-Kai; Yan, Shuai-Lei; Zhao, Chen-Xi; Liu, Xiao-Hui; Sun, Han-Wen (Asian Journal of Chemistry, 2012)
A new method for synthesis of the restricted access material-molecularly imprinted polymer was developed. Based on self-assembly and sol-gel technique, restricted access materialmolecularly imprinted polymer was prepared by self-hydrolyzed, self-condensed and co-condensation of tetraethoxysilane and (octyl)-trimethoxysilane (C8-TMS) in the presence of lomefloxacin and surfactant micelles and with the covalently anchored organic groups in the mesoporous silica matrix. The surface of the silica matrix was modified by g-(2,3-epoxypropoxy) propyltrimethoxysilane (KH-560) to enhance the hydrophilic properties. The recognition and hydrophilic properties of the restricted access material-molecularly imprinted polymer were evaluated by binding study and the swelling degree measurements and the molecularly imprinted mesoporous silica was used for comparison. Both specific interactions between template and restricted access material-molecularly imprinted polymer and the recovery of bovine serum albumin increased obviously. The recovery of bovine serum albumin was higher than 99 %.